Ifosfamide in the treatment of ovarian cancer - Obrębowska, Anna; Sajdak, Stefan (Contemporary Oncology/Współczesna Onkologia, 1999)
Ifosfamide is an antineoplastic drug, which is used in chemotherapy of gynecological cancers. Special place has ifosfamide in the treatment of ovarian cancer, both in singleagent therapy and in combination with cis-platin. More recently, trias have been conducted to study the use of ifosfamide in high-dose chemotherapy with autologous bone marrow transplantation. In thsi article results of chemotherapy with ifosfamide as a second line treatment in advanced ovarian cancer are presented.